Comanthus kumi, a new shallow-water comatulid (Echinodermata: Crinoidea: Comatulida: Comasteridae) from the Ryukyu Islands, Japan - Fujita, Yoshihisa; Obuchi, Masami (Zootaxa, 2012)
A new species of the genus Comanthus A.H. Clark, 1908, is described on the basis of specimens collected from KumeIsland and Okinawa Island, the Ryukyu Islands, Japan. Comanthus kumi n. sp. is distinguished from all ten congeners byhaving extremely elongate arms exceeding 300 mm in length and the colouration in life. The new species concealed itswhole body in a crevice or small hole on coral reefs during the day and protruded only several elongate arms on the reef surface at night. This habit suggests that the new species is nocturnal.